A CLEAN PAIR OF HEELS; LEUKODYSTROPHY IN A 40 YEAR OLD MALE. Issue 10 (9th September 2014) - Reynolds, Lucy; Mackinnon, Andrew; Metta, Vinod; Warner, Graham
Abstract : A 40 year old man presented with a slowly progressive history of worsening gait unsteadiness and cognitive decline for further review, following several recent falls. A spastic paraparesis was present on examination, without cerebellar or extrapyramidal signs. Previous and current imaging was reexamined and found to be consistent with leukodystrophy despite previously being reported as 'normal'. Retrospective history of first cousin marriage and the patient's bilateral juvenile cataract removal was elicited from his family. Cerebrotendinous xanthomatosis was subsequently diagnosed on biochemical testing and despite lack of tendon xanthomata.